Ideas and perspectives: How sediment archives can improve model projections of marine ecosystem change - I. Hochfeld; B. A. Ward; A. Kremp; J. Romahn; J. Romahn; J. Romahn; A. Schmidt; A. Schmidt; M. Bálint; M. Bálint; M. Bálint; L. Becks; et al. (Biogeosciences)
Global warming is a major threat to marine biodiversity and ecosystem functioning, with consequences that are yet largely unknown. To frame these consequences, we need to understand how marine ecosystems respond to warming and related environmental changes. Ecosystem models have proven to be a valuable tool in this respect, but their projections vary considerably. A major limitation in current ecosystem models may be that they largely ignore evolutionary processes, which nonetheless can be relevant on the simulated timescales. In addition, ecosystem models are usually fit to contemporary data and used predictively afterwards, without further validation that they are equally applicable to past (and, by inference, future) scenarios. A promising approach to validate evolutionary ecosystem models is the use of biological archives such as natural sediments, which record long-term ecosystem changes. Since the ecosystem changes present in sediment records are affected by evolution, evolution needs to be represented in ecosystem models not only to realistically simulate the future, but also the sediment record itself. The sediment record, in turn, can provide the required constraints on long-term evolutionary changes, along with information on past environmental conditions, biodiversity, and relative abundances of taxa. Here, we present a framework to make use of such information to validate evolutionary ecosystem models and improve model projections of future ecosystem changes. Using the example of phytoplankton, key players in marine systems, we review the existing literature and discuss (I) which data can be derived from ancient sedimentary archives, (II) how we can integrate these data into evolutionary ecosystem models to improve their projections of climate-driven ecosystem changes, and (III) future perspectives and aspects that remain challenging.